2012
DOI: 10.5194/aab-55-325-2012
|View full text |Cite
|
Sign up to set email alerts
|

Crowding of dairy cows in a cubicle barn during the hot summer months

Abstract: Abstract. This study was carried out on a commercial dairy farm located in the South-Moravian region of the Czech Republic. Two video cameras (IP7330 and PZ6122, Vivotek Technology), located over cubicles below the ceiling, provided video recordings, which were taken in 15-min intervals from 02.00 to 08.00 (Period 1 – morning) and from 10.00 to 19.30 (Period 2 – afternoon) one day per week (i.e. on Thursday) from 2 July (week 27) to 15 October (week 42). Air temperatures and humidity were measured every fiftee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…Zahrádková et al (2009) pointed out that standing has a cooling eff ect, because it enhances evaporation from the body surface. Our results are comparable to those of Erbez et al (2012), who found out that the cows in loose housing with stalls tend to form groups and crowd during the summer months. Crowding of the cows exposed to high air temperatures is thought to be unusual.…”
Section: Resultssupporting
confidence: 90%
“…Zahrádková et al (2009) pointed out that standing has a cooling eff ect, because it enhances evaporation from the body surface. Our results are comparable to those of Erbez et al (2012), who found out that the cows in loose housing with stalls tend to form groups and crowd during the summer months. Crowding of the cows exposed to high air temperatures is thought to be unusual.…”
Section: Resultssupporting
confidence: 90%
“…Berman et al (1985) claim that the thermal load of animal could be affected by factors like housing system, location of animal and social rank. When the temperature and humidity are both high the influence on feed intake, reproduction and milk production is negative (Erbez et al, 2012). According to Vokřálová et al (2007) the thermoneutral zone for cattle is between −5 °C and +24 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the year, the side walls of the barn are permanently open. In this barn, ERBEZ et al (2012) and VEČEŘA et al (2011) also did their research.…”
Section: Methodsmentioning
confidence: 81%